PELAKSANAAN SUPERVISI AKADEMIK SEKOLAH MENENGAH PERTAMA NEGERI SE-KECAMATAN KOTO TANGAH KOTA PADANG - LINDA PERMATA SARI (Jurnal Bahana Manajemen Pendidikan, 2016)
In the purpose of this research was to look at the information on the implementation of the academic supervision with a population of 289 teachers and 60 samples were taken using proportional stratified random sampling. The research instrument is a question with a Likert scale models that have been tested for validity and reliability using SPSS version 16. The data is analyzed  by comparing the average. The results of this study is about the implementation of the academic supervision in Junior High School district throughout koto tangah of the city of Padang in both categories.